NANOCELLULOSE-ENHANCED POLY (LACTIC-CO-GLYCOLIC) ACID AS A SYNTHETIC GRAFT MATERIAL FOR IMPROVED BONE AUGMENTATION: A SYSTEMATIC REVIEW - RAKHMATIA, YUNIA DWI; INDRAWAN, RIFA KHALISHA; DAMAYANTI, LISDA; NOVIANTI, VITA MULYA PASSA; HASTUTI, NOVITRI (International Journal of Applied Pharmaceutics, 2025)
A pre-implantation bone graft provides structural support when alveolar bone is insufficient. This study investigates nanocellulose and poly(lactic-co-glycolic acid) (PLGA) as grafting materials. PLGA enhances scaffold degradability through hydrolytic cleavage, with degradation kinetics determined by its lactic acid to glycolic acid (LA: GA) ratio. A 50:50 ratio degrades fastest (~8 w), while a 75:25 ratio slows degradation (~16 w). Nanocellulose, while being poorly degradable in vivo, improves mechanical strength and hydrophilicity. PLGA/CNF scaffolds showed 95% porosity with through-pores (20–100 µm), promoting cell infiltration. Mechanical strength improved with nanocellulose: compressive strength increased from 4.0 MPa (PLGA) to 6.4 MPa (PLGA/CMC), and elastic modulus reached 1,240±40 MPa in PVA/PLGA/CNC composites—a 42-fold increase. Good biocompatibility was found in all the composite samples examined, and osteogenesis was promoted. In vitro and in vivo studies confirmed that PLGA compensates for nanocellulose’s limited degradability, with complete scaffold resorption observed within 12 w for 50:50 PLGA and within three months for CPC/PLGA/CMC in PBS. These results highlight the synergistic potential of PLGA/nanocellulose composites for bone tissue engineering by combining tunable degradability, enhanced mechanics, and strong biocompatibility.